From FIMC to Masq’Alors: reflections on community experiences of a mask theater (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
This study aims to revisit the exchange experiences experienced by the Máscara Encena group through the participation of the show Imobilhados in two twin festivals: FIMC (Cariri International Mask Festival - Brazil) and Masq'Alors (Quebec International Mask Festival - Canada). Based on these experiences, this text aims to reflect on the role of masked theater in strengthening community identity, cultural traditions, knowledge, and celebrations inspired by such initiatives, taking as a starting point the group's performances at these festivals between 2018 and 2019.Keywords: Masked theater festivals; community identity; cultural exchange; Máscara EnCena group.
Keywords: masked theater festival; community identity; cultural exchange; máscara EnCena group